2015
DOI: 10.4103/0972-5229.171352
|View full text |Cite
|
Sign up to set email alerts
|

Can integrative weaning index be a routine predictor for weaning success?

Abstract: Objective:To assess the effectiveness of integrative weaning index (IWI) as a predictor of weaning success.Materials and Methods:This is a prospective randomized controlled observer-blinded study and carried out on 120 patients of both sexes; patients who received mechanical ventilation for more than 24 h and met defined criteria for a weaning trial, underwent a 2-h spontaneous breathing trial with either IWI plus routine criteria of weaning (Group I n = 60) or routine criteria of weaning alone (control group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…However, several studies have introduced this index as a desirable tool for predicting the weaning outcome reporting 90%–97% sensitivity, 66.7%–94% specificity, a PPV of 90%–99%, NPV of 50%–93%, and an accuracy of 87%–92%. [ 3 10 14 16 ] As the comparison of these data shows, except for the specificity reported by the current study which is lower than the lowest level reported in the previous studies, other studied parameters are in the same range as previous reports.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, several studies have introduced this index as a desirable tool for predicting the weaning outcome reporting 90%–97% sensitivity, 66.7%–94% specificity, a PPV of 90%–99%, NPV of 50%–93%, and an accuracy of 87%–92%. [ 3 10 14 16 ] As the comparison of these data shows, except for the specificity reported by the current study which is lower than the lowest level reported in the previous studies, other studied parameters are in the same range as previous reports.…”
Section: Discussionsupporting
confidence: 67%
“…The reported range for the IWI positive and NLR in different studies is 2.84, 16.5, 0.03–0.12, respectively. [ 3 10 14 16 ] The only point which can justify the inconsistency in these findings is the difference in study design and the association between the likelihood ratio and the specificity parameter which was less in the current study in comparison to other studies. And last but not least is the IWI accuracy which was similar to the values reported by other studies.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…17,23 On the other hand, the IWI, which can evaluate multiple essential functions, such as f/V T , compliance of the respiratory system, and oxygenation, presented higher predictive performance in a general population in the study of Nemer et al 11 and in the current study too. The IWI has been cited in several review studies, 11,[24][25][26][27] described as highly accurate, 11,25,26 and recommended by the Brazilian guidelines on mechanical ventilation. 24 Besides these advantages, the IWI can be measured regardless of the subject's cooperation.…”
Section: Discussionmentioning
confidence: 99%